Partial discharge detection system for counting PD signals in high voltage underground cable by using FPGA technology - Emilliano; Chakrabarty C.K.; Ramasamy A.K.; Ghani A.B.A. (2023)
Currently, FPGA (Field Programmable Gate Array) technology is being widely used for signal processing and control owing to its fast digital processing capability. We have recently developed successfully a high-speed data acquisition system that combines a commercial FPGA board (ML405) with the high speed ADC in ADC 083000RB that has 8 bit pairs LVDS in resolution, sampling rate of 3 GS/s and bandwidth of 3 GHz for counting very high speed transient signals. The programming is in VHDL. This system enables direct measurement and counting of transient signals at 1-10 ns pulse width at a sampling frequency 3 GHz. The partial discharge (PD) signals in this work are simulated by using Pico Pulse generator. All the counting is performed in the FPGA without the use of oscilloscope. The count rates are displayed in the LCD monitor of the FPGA hence rendering it to be highly mobile. 2011 Institute of Electrical Power.